Optimalisasi Perencanaan Dan Pengendalian Produksi Rak Palet Menggunakan Metode Cutting Plane - Fadilla Umeida Putri; RR. Rochmoeljati (International Forum of Researchers and Lecturers, 2024)
PT Atlantic Anugrah Metalindo is a manufacturing company that produces costumize products, steel door systems and fireproof doors. Currently PT Atlantic Anugrah Metalindo is producing 100 units of pallet rack manufacturing with customers from PT X so that proper material requirements planning is needed. The purpose of this research is to determine the material requirements of pallet racks optimally and efficiently. This research requires calculating the Bill of Materials (BOM) using the Cutting plane method and controlling the production process to run effectively and efficiently. Based on the calculations that have been carried out, the results show that for 2 mm thick mild steel material requirements, 6 sheets of plate are needed, 3 mm thick mild steel requires 173 sheets of plate, 3.6 mm thick mild steel requires 12 sheets of plate and 5 mm thick mild steel requires 12 sheets of plate. So that from these calculations PT Atlantic Anugrah Metalindo is expected to minimize the material requirements of pallet rack products.